Infantile Spasms: An Update on Pre-Clinical Models and EEG Mechanisms - Remi Janicot; Li-Rong Shao; Carl E. Stafstrom (MDPI AG, 2020)
Infantile spasms (IS) is an epileptic encephalopathy with unique clinical and electrographic features, which affects children in the middle of the first year of life. The pathophysiology of IS remains incompletely understood, despite the heterogeneity of IS etiologies, more than 200 of which are known. In particular, the neurobiological basis of why multiple etiologies converge to a relatively similar clinical presentation has defied explanation. Treatment options for this form of epilepsy, which has been described as “catastrophic” because of the poor cognitive, developmental, and epileptic prognosis, are limited and not fully effective. Until the pathophysiology of IS is better clarified, novel treatments will not be forthcoming, and preclinical (animal) models are essential for advancing this knowledge. Here, we review preclinical IS models, update information regarding already existing models, describe some novel models, and discuss exciting new data that promises to advance understanding of the cellular mechanisms underlying the specific EEG changes seen in IS—interictal hypsarrhythmia and ictal electrodecrement.